A Randomized Controlled-feeding Trial Based on the Dietary Guidelines for Americans Does Not Affect Plasma Trimethylamine N-oxide Levels in Women (P08-031-19) - Bennett, Brian (Curr Dev Nutr, 2019)
OBJECTIVES: Trimethylamine N-oxide is a gut-mediated metabolite associated with cardiovascular disease. Acute diet challenges demonstrate that circulating TMAO concentrations are diet-responsive; however, long-term trials investigating how different dietary patterns affect circulating TMAO concentrations are sparse. The objective of the current study was to determine whether consumption of a diet patterned after the USDA's 2010 Dietary Guidelines for Americans (DGA), as compared to the typical American Diet (TAD), would reduce plasma TMAO levels. METHODS: A randomized, double-blind, controlled 8-wk intervention was conducted in overweight and obese women selected according to indexes of insulin resistance or dyslipidemia. Women were randomly assigned to the DGA or TAD group (n = 28 DGA and 24 TAD). The TAD diet was based on average adult intake from the NHANES 2009–2010. All foods and beverages were provided during the intervention and matched to each participant's energy requirement to ensure maintenance of initial body weight.Plasma samples were collected at baseline, 1 wk of their typical diet, and after 2 and 8 weeks of dietary intervention, in an overnight-fasted condition, and utilized to quantitate circulating TMAO concentrations using stable isotope dilution chromatography tandem mass spectrometry. Statistical analysis were performed in SAS using analysis of covariance and partial correlation. RESULTS: Following 2 or 8 weeks of dietary intervention, plasma TMAO concentrations were not different between the DGA and TAD diets (3.45 ± 0.41 vs 2.91 ± 0.38 μM at week 2; 3.48 ± 0.41 vs 3.00 ± 0.40 μM at week 8, Mean ± SE, respectively). Post-intervention TMAO concentration was correlated to initial TMAO concentrations and body mass index but not age. Furthermore, we did not observe significant correlations between TMAO and measures of endothelial function (Endopat) or insulin resistance (HOMA-IR) which may reflect the relative health of the overall population enrolled in the study. CONCLUSIONS: Consumption of a diet based on the USDA's 2010 Dietary Guidelines for Americansfor 8 weeks did not reduce plasma TMAO levels in this study. FUNDING SOURCES: Supported by National Dairy Council; Campbell Soup Co.; USDA-ARS Projects 2032-51530-022-00D and 6026-51000-010-05S.